2019
DOI: 10.1021/acsomega.9b02541
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sensing of pH and O2 in the Evaluation of Bioactive Self-Healing Cement

Abstract: Leakage from cementitious structures with a retaining function can have devastating environmental consequences. Leaks can originate from cracks within the hardened cementitious material that is supposed to seal the structure off from the surrounding environment. Bioactive self-healing concretes containing bacteria capable of microbially inducing CaCO3 precipitation have been suggested to mitigate the healing of such cracks before leaking occurs. An important parameter determining the biocompatibility of concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“… 1249 Also an aza-BODIPY pH indicator was used in a ratiometric approach using a single-lens reflex camera instead of a gated CCD camera. 1250 The system was used to characterize the pH of porewater within cracks of self-healing concrete materials. It enabled imaging of pH with a high resolution (50 μm per pixel) and a gradient of 1.4 pH units per 1 mm.…”
Section: Selected Applications Of Optical Ph Sensorsmentioning
confidence: 99%
“… 1249 Also an aza-BODIPY pH indicator was used in a ratiometric approach using a single-lens reflex camera instead of a gated CCD camera. 1250 The system was used to characterize the pH of porewater within cracks of self-healing concrete materials. It enabled imaging of pH with a high resolution (50 μm per pixel) and a gradient of 1.4 pH units per 1 mm.…”
Section: Selected Applications Of Optical Ph Sensorsmentioning
confidence: 99%
“…47 Some fluoroionophores are also similar to the well-known fluorescent indicators such as Fura-2 for Ca 2+ and SBFI for Na + except that they are typically hydrophobic. 48,49 The groups of Wolfbeis, 50−54 Borisov, 55−59 Klimant, 60,61 and Koren 62,63 have reported many ion optodes by incorporating fluoroionophores into hydrogels. These thin-film optodes exhibited reversible responses and are well suited for continuous monitoring and 2D imaging of environmental or clinical samples.…”
Section: ■ Ionophore-based Hydrogel-nanocomposites As Ion Sensorsmentioning
confidence: 99%
“…The group of Wolfbeis demonstrated that POs can be valuable tools in medical research, in particular to find infections by imaging the chemical composition of wounds. , Others used POs in material research enabling, e.g. , pH monitoring of concrete , to find areas where the chemical composition is altered. Also in soil sciences, researchers now use POs to visualize microenvironments and to follow the distribution of important analytes , linking the chemical microenvironments to nutrient uptake and nutrient fluxes.…”
Section: What Are the Possibilities Of Optode Based Chemical Imaging?mentioning
confidence: 99%